Total rhinectomy for nasal carcinomas - Girardi,Fábio Muradás (2020)
Abstract Introduction: Total rhinectomy is an uncommon procedure for the treatment of nasal malignancies, usually reserved for locally advanced tumors. There are few case series studying total rhinectomy in the literature, reporting conflicting results about recurrence and metastasis. Objective: Evaluate prognosis of total rhinectomy cases for malignant neoplasia in our institution. Methods: Retrospective review from January 2013 to September 2018, including all patients undergoing total rhinectomy in our Institution, under the care of the Head and Neck surgical team. Results: Ten patients were included, two men and eight women. The mean patient age was 71.6 years old. The majority had nasal skin (8 cases) carcinomas. Squamous cell carcinoma was present in seven cases. In total, six cases had regional metastasis, in a median period of 14.3 months. The overall mortality and disease specific mortality was 50% and 30%, respectively, in a median follow-up of 45.7 months. Conclusion: We observed high overall and disease-specific mortality among cases with advanced nasal malignancies undergoing total rhinectomy.